1994
DOI: 10.1111/j.1439-0523.1994.tb00673.x
|View full text |Cite
|
Sign up to set email alerts
|

A Greenhouse Method to Assess Sunflower Resistance to Sclerotinia Root and Basal Stem Infections

Abstract: A method was developed to assess sunflower resistance to sclerotinia root infections in greenhouses. Some of the genotypes were also tested in the field to validate the greenhouse testing method. Efficiency of this method was also tested in a diallel cross. The susceptibility could be assessed by the final percentage of dead plants or by the time required to reach a given threshold of attack (threshold latency parameter). The correlation coefficients between susceptibility assessed in the field and with the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
(8 reference statements)
1
4
0
Order By: Relevance
“…The contribution to the total variation of the lines, testers, and their interactions support prior results that general effects were more relevant than specific effects for Sclerotinia rot resistance [ 59 , 61 , 62 ]. On the other hand, specific effects had a greater impact on yield component traits and oil content [ 9 , 11 , 54 , 57 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The contribution to the total variation of the lines, testers, and their interactions support prior results that general effects were more relevant than specific effects for Sclerotinia rot resistance [ 59 , 61 , 62 ]. On the other hand, specific effects had a greater impact on yield component traits and oil content [ 9 , 11 , 54 , 57 ].…”
Section: Discussionsupporting
confidence: 81%
“…Kaur et al [ 53 ], Meena et al [ 54 , 55 , 56 ], Vaghela et al [ 57 ], Chaudhary et al [ 58 ], and Gupta et al [ 9 ] observed high genetic variability for yield and its component traits in Indian mustard. Godoy et al [ 59 ], Castano et al [ 60 ], Achbani et al [ 61 ], and Grecizes-Besset et al [ 62 ] in sunflower and Ferreira et al [ 63 ] in common bean revealed high genetic variability for resistance/susceptibility to S. sclerotiorum .…”
Section: Discussionmentioning
confidence: 99%
“…Most papers show genetic effects preponderantly additive for disease resistance when single hybrids were artificially infected by S. sclerotiorum on plant organs such as capitula [13,19,27], leaves [5], terminal buds [1], basal stem [14] and cotyledons [24]. Conversely, Vrânceanu et al [28] showed strong SCA effects for resistance to mycelium infection of Sclerotinia basal attack in sunflower germplasm and Pîrvu et al [16] detected two inbred lines with a single recessive gene controlling mechanical resistance to initial penetration of the stem-surface tissues by Sclerotinia mycelium.…”
Section: Discussionmentioning
confidence: 99%
“…It would therefore be of great interest to use other S. sclerotiorum resistance tests more rapid and easy, particularly in those sunflower breeding programmes with a lack of resources. Research has been developed to successfully produce S. sclerotiorum infections on sunflower seedlings of inbred lines and hybrids under controlled conditions [3,14,17,22], but segregating and heterogeneous populations have not yet been used. The interest of such studies lies in the possibility of their direct use in sunflower breeding programmes for white rot resistance.…”
Section: Articlementioning
confidence: 99%
“…To achieve the benefit from herbal drugs, a person must take the mandatory dose over a certain period of time. Generally, it is believed that herbal drugs are safe for consumption but some herbs like most biologically active substances could be toxic with undesirable side effects (Grezes-Besset et al, 1994). A safe, well-defined and constant composition is one of the most important prerequisites for the production of a quality herbal drugs and ensuring consistent quality of products is vital for the survival and success of the herbal industry (Bauer, 1998).…”
Section: Invited Commentarymentioning
confidence: 99%